HEPATIC TISSUE ENGINEERING (MODERN STATE OF THIS PROBLEM) - Y.S. Gulay; M.E. Krasheninnikov; M.Y. Shagidulin; N.A. Onishchenko (Вестник трансплантологии и искусственных органов, 2014)
In this article it was discussed the problem of creation implanted hepatic tissue engineering designs as a modern stage of complex investigation for working out bioartifi cial liver support systems. It was determined that for the positive decision of numerous biological and technological problems it is necessary: to use matrices with determined properties, which mimic properties of hepatic extracellular matrix; to use technology for stereotype sowing of these matrices by both parenchymal and non-parenchymal hepatic cells and to improve the technologies for making and assembling of hepatic tissue-engineering designs.